Long non-coding RNA MALAT1 promotes steatosis in HepG2 cells by modulating target gene expression in presence of Exendin-4 - Olfa Khalifa (10914452) (2023)
Poster by Olfa Khalifa (Hamad Bin Khalifa University), Khaoula Errafii (Mohammed VI Polytechnic University), Sama Ayoub (Weill Cornell Medicine - Qatar), Abdelilah Arredouani (Hamad Bin Khalifa University) Background: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide in part due to the obesity epidemic and insulin resistance. The mechanisms underlying the non-alcoholic steatosis are poorly understood and little information is available on the pathways responsible for the progressive hepatocellular damage that follows lipids accumulation. NAFLD research is incredibly important because its diagnosis requires the conduction of a biopsy. Accordingly, more recently biomarkers including noncoding RNAs have been investigated for their involvement in the disease. There are several types of noncoding RNAs associated with NAFLD. Long noncoding RNAs (LncRNAs), which include more than 200 nucleotides, have a role in a range of biological processes including cell proliferation, death, and differentiation. MALAT1 (metastasis associated with lung adenocarcinoma transcript 1) is a well-conserved lncRNA that has been linked to a variety of illnesses, including cancer. However, its role in hepatic steatosis and lipid accumulation is unknown. MALAT1 has recently attracted attention for its role in the evolution of diabetic complications, since it has been demonstrated that MALAT1 dysregulation contributes to the pathogenesis of diabetes and liver disease.  Objective: The purpose of this study was to investigate MALAT1's effects on hepatic lipid accumulation and potential targets in presence of the GLP-1R agonist Exendin-4 (Ex-4), which has the potential to improve steatosis and even steatohepatitis. Methods: A steatosis cell model was established using HepG2 cells by treating them overnight with 400 mM oleic acid (OA). We determined the optimal concentration of OA needed to obtain saturating levels of triglycerides. Then starved the cells for 6h in DMEM containing 1% fatty-acid-free bovine serum albumin. Following the starvation, a 16h incubation in DMEM containing increasing concentrations of OA (0–500 µM) at 37 °C was performed, and steatosis was quantified by triglycerides quantification, Bodipy staining, and quantification of the expression of perilipin genes family. The transcriptomic profiling was performed using total RNA extracted from untreated, steatotic and Ex-4-treated steatotic, cells. We validated a subset of differentially expressed LncRNAs with qRT-PCR and identified the most significantly enriched cellular functions associated with the relevant LncRNAs, among them MALAT1. Finally, CD36 was silenced, and lipogenesis genes expression were quantified using q-PCR and/or western blots. Results: Treatment with 200nM Ex-4 for 3h decreased the OA-induced lipid buildup significantly (p<0.05). Concurrently, Ex-4 significantly lowered the expression levels of De novo lipogenesis genes such as SREBP-1, SCD-1and ACC. In the presence of Ex-4, the expression of PLIN2 and PLIN3, but not PLIN1, was significantly lower than OA alone, indicating that Ex-4 reduces the number of lipid droplets, and thus the lipid content. Furthermore, confocal microscopy analysis of BODIPY-stained untreated, steatotic, and Ex-4-treated steatotic cells showed that Ex-4 significantly decreases the number of lipid droplets. Fatty acid uptake and transport genes were also affected by MALAT1 knockdown. Moreover, MALAT1 knockdown dramatically suppressed oleic-induced lipid accumulation in HepG2 cells. Interestingly, knocking down MALAT1 significantly reduces the expression of CD36 in steatosis HepG2 cells in the presence of Ex-4. Finally, the silencing of MALAT1 prevented hepatic lipid accumulation in HepG2 cells.